Sonntags-abschied (Sunday-Farewell): A report - Toop, Richard (Kürten Stockhausen Verlag, 2005)
Richard Toop: SONNTAGS - ABSCHIED ( SUNDAY FAREWELL ) - a Report( 22 pages in English with numerous musical examples and 2 colour photographs )
Keywords: Stockhausen, Karlheinz -- 1928-2007; 21st Century (2001-2100)